Optimalisasi Pemasaran Digital bagi UMKM Wedang Uwuh di Bantul untuk Meningkatkan Daya Saing dan Penjualan - Ika Menarianti; Shofif S. Akbar; I’tishom Al Khoiry; Ernawati Saptaningrum (Jurnal Pengabdian kepada Masyarakat Indonesia (JPKMI), 2025)
Digital capacity building through training and digital marketing mentoring is necessary for Wedang Uwuh MSMEs in Wukirsari Village. Their potential is still underdeveloped, particularly in marketing. This beneficial traditional herbal beverage product still faces challenges due to a lack of digital literacy, e-commerce management constraints, and content strategy. This activity focused on five stages of community service: observation, material development, training and mentoring, and monitoring and evaluation. As a result, the business owners now have Google My Business, social media accounts, and e-commerce platform accounts. This activity fosters the branding of their products, expanding market reach, and enhancing the competitiveness of local, culture-based products.